Gastronomy and Culinary Arts Students’ Gastronomy, Culinary, and Art Perception: A Metaphor Analysis - Ertaş, Çağdaş; Nur, Taner (My University, 2025)
This study explores the gastronomy and culinary arts students’ metaphorical perceptions of gastronomy, culinary, and art. Using a qualitative phenomenological research design, the study employed semi-structured interviews with purposively selected students to uncover the cognitive, cultural, and emotional frameworks shaping their understanding of these concepts. Findings reveal that students perceive gastronomy as a fusion of art, science, and cultural expression, frequently conceptualizing it through metaphors such as a journey, a laboratory, and a canvas of creativity. Culinary are framed within themes of discipline, exploration, and craftsmanship, while art is metaphorically linked to expression, identity, and transformation. The study contributes to gastronmy and culinary arts education by highlighting the pedagogical implications of metaphorical thinking. The research underscores the potential for cross-cultural studies in metaphorical perceptions of gastronomy and culinary arts, offering avenues for future research.
Keywords: Qualitative research; Gastronomy education; Culinary arts; Metaphor analysis; Cognitive Metaphor Theory